Global Robots - Fabrizio Leone (CESifo GmbH, 2024)
The diffusion of automation technology raises questions about the future of work, leading to calls for policy interventions. The ongoing debate centers on the decisions made by technology adopters. In this paper, I study supply-side adjustments and their role in shaping policy outcomes. I focus on the global market for industrial robots, a leading type of automation technology, where a few multinational enterprises (MNEs) dominate sales. To evaluate how these MNEs respond to policy changes, I collect new data on their characteristics and global sales networks. I then develop and estimate a multi-country general equilibrium model featuring oligopolistic multinational robot sellers. Using this model, I find that MNEs' market entry and pricing responses transmit internationally and amplify the aggregate and distributional effects of policies targeting robots.
Keywords: F10; F16; F23; L13; O33; 330; multinational enterprises; market power; automation